Ultraviolet sensitivity in Higgs-Starobinsky inflation - Lee, Sung Mook; Modak, Tanmoy; Oda, Kin-ya; Takahashi, Tomo (Journal of cosmology and astroparticle physics, 2023)
The general scalar-tensor theory that includes all the dimension-four terms has parameter regions that can produce successful inflation consistent with cosmological observations. This theory is in fact the same as the Higgs-Starobinsky inflation, when the scalar is identified with the Standard Model Higgs boson. We consider possible dimension-six operators constructed from non-derivative terms of the scalar field and the Ricci scalar as perturbations. We investigate how much suppression is required for these operators to avoid disrupting the successful inflationary predictions. To ensure viable cosmological predictions, the suppression scale for the sixth power of the scalar should be as high as the Planck scale. For the other terms, much smaller scales are sufficient.
Veröffentlicht: 18. August 2023
Gesehen am 27.10.2023